Evidence-based practices and treatments in autism spectrum disorder: concluding thoughts - Volkmar, F.R.; Doehring, P.; Reichow, B. (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
This concluding chapter summarizes how the field has advanced, the current state of evidence-based practices, unique insights derived from systematic reviews of practices and programs, and directions for the future. We note major gains since the first attempts in the early 1990s to provide information on evidence-based practices, including more sophisticated research methods for meta-analytic studies and systematic reviews. The emergence of very high-quality reviews of rigorous outcome research over the past 15 years has accelerated interest in evidence-based practices. At the same time, controversies surrounding questions of research design, study selection, the potential bias relative to cultural and racial factors, persistent gaps in research on adults and those with more significant levels of disability, and other areas remain to be addressed. We note some area of active discussion, e.g., relative to whether or not to screen and the need to help community-based professionals responsible for tailoring evidence-based practices to the many different individuals and settings they serve. If we are able to reconcile the researcher’s desire for experimental rigor with the flexibility required for outcome studies conducted in community-based settings, we might begin to demonstrate the kinds of population impacts needed to justify more substantial funding and policy changes. Several areas of additional research are outlined. © Springer Nature Switzerland AG 2025.
Keywords: Eclectic programs; Evidence-based treatment; Future directions; Meta-analyses; Systematic reviews; dept.sed